Observations of a Solar Energetic Particle Event From Inside and Outside the Coma of Comet 67P. Issue 12 (29th November 2022) - Wellbrock, A.; Jones, G. H.; Dresing, N.; Coates, A. J.; Simon Wedlund, C.; Nilsson, H.; Sanchez‐Cano, B.; Palmerio, E.; Turc, L.; Myllys, M.; Henri, P.; Goetz, C.; et al.
Abstract: We analyze observations of a solar energetic particle (SEP) event at Rosetta's target comet 67P/Churyumov‐Gerasimenko during 6–10 March 2015. The comet was 2.15 AU from the Sun, with the Rosetta spacecraft approximately 70 km from the nucleus placing it deep inside the comet's coma and allowing us to study its response. The Eastern flank of an interplanetary coronal mass ejection (ICME) also encountered Rosetta on 6 and 7 March. Rosetta Plasma Consortium data indicate increases in ionization rates, and cometary water group pickup ions exceeding 1 keV. Increased charge exchange reactions between solar wind ions and cometary neutrals also indicate increased upstream neutral populations consistent with enhanced SEP induced surface activity. In addition, the most intense parts of the event coincide with observations interpreted as an infant cometary bow shock, indicating that the SEPs may have enhanced the formation and/or intensified the observations. These solar transient events may also have pushed the cometopause closer to the nucleus. We track and discuss characteristics of the SEP event using remote observations by SOHO, WIND, and GOES at the Sun, in situ measurements at Solar Terrestrial Relations Observatory Ahead, Mars and Rosetta, and ENLIL modeling. Based on its relatively prolonged duration, gradual and anisotropic nature, and broad angular spread in the heliosphere, we determine the main particle acceleration source to be a distant ICME which emerged from the Sun on 6 March 2015 and was detected locally in the Martian ionosphere but was never encountered by 67P directly. The ICME's shock produced SEPs for several days which traveled to the in situ observation sites via magnetic field line connections. Key Points: We track a solar energetic particle (SEP) event in situ at Solar Terrestrial Relations Observatory Ahead, Mars and Rosetta and determine the main source to be a non‐local interplanetary coronal mass ejection shock distant to 67P Increased solar wind charge exchange at 67P may indicate an increase in upstream neutral populations and associated SEP induced sputtering The most intense parts of the SEP event at 67P coincide with observations of an infant bow shock and may have enhanced its formation